1993
DOI: 10.1139/g93-128
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of minisatellite sequences from Oryza sativa

Abstract: Two DNA sequences were cloned from the genome of cultivated rice (Oryza sativa L.) by cross-hybridization with the human minisatellite sequence 33.6. The rice sequences consisted of tandem direct repeats, which showed significant similarity to the 33.6 consensus sequence. Profiles capable of distinguishing different rice cultivars were detected by cross-hybridization with a DNA probe amplified by the polymerase chain reaction from one of the rice minisatellite sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Thus, a relatively large degree of variation in the number of repeats was observed among loci of both GC-rich and AT-rich MSs contained in The range was indicated when the number of copies detected was two or more than two in each TE group Fig. 1 The En / Spm -like element TEOS6.2H containing minisatellite pOs6.2H reported by Winberg et al (1993). The sequences of the three members belonging to this TE group and the minisatellite pOs6.…”
Section: Variation In Repeat Numbers Among Mss In Dasheng and Bashomentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, a relatively large degree of variation in the number of repeats was observed among loci of both GC-rich and AT-rich MSs contained in The range was indicated when the number of copies detected was two or more than two in each TE group Fig. 1 The En / Spm -like element TEOS6.2H containing minisatellite pOs6.2H reported by Winberg et al (1993). The sequences of the three members belonging to this TE group and the minisatellite pOs6.…”
Section: Variation In Repeat Numbers Among Mss In Dasheng and Bashomentioning
confidence: 92%
“…Winberg et al (1993) first isolated and characterized the GC-rich MS pOs6.2H from rice genomic DNA by using the human MS DNA 33.6 as a probe (Jeffreys et al 1985). This rice MS showed multi-banding patterns in Southern hybridization analysis at high stringency (Winberg et al 1993), and when the multiple loci were mapped, they were found to occur throughout the rice chromosomes (Gustafson and Yano 2000). These data strongly suggested that the MS pOs6.2H was also associated with a TE.…”
mentioning
confidence: 99%
“…Thus, in cereals, repetitive sequences can constitute more than 75% of the genome (Guidet et al 1991). In general, repetitive DNA sequences in plant genomes consist of satellites (Gupta et al 1990; Kamm et al 1995), minisatellites (Winberg et al 1993), microsatellites (Panaud et al 1995), and interspersed elements, including transposable elements such as retrotransposons (Flavell et al 1992;Voytas et al 1992; Leeton and Smyth 1993;Kolchinsky and Gresshoff1995). In recent years, repetitive DNA sequences have been cloned from various economically important plant species, characterized molecularly, and used as DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of the reported repetitive elements are species-or genome-specific (Jiang et al 1996). In plant genomes, repetitive DNA sequences consist of satellites (Kamm et al 1995), minisatellites (Winberg et al 1993), microsatellites (Panaud et al 1995), and interspersed elements that include transposable elements, such as retrotransposons (Kolchinsky and Gresshoff 1995). Tandemly repeated sequences (satellite DNA) in plants normally have a characteristic chromosomal location: subtelomeric, interspersed or centromeric, with blocks of each motif present on some or all chro- J Appl Genet 48(3), 2007, pp.…”
Section: Introductionmentioning
confidence: 99%